Pelatihan Pembuatan Kompos dari Daun dan Ampas Tebu Sebagai Upaya Pemanfaatan Limbah Pertanian - Irwandi Rahmat; Salma Samputri; Akhmad Syakur; Sahrani U; Muh. Tawil (JKM: Jurnal Kemitraan Masyarakat, 2025)
This community service program aimed to enhance the knowledge, skills, and attitudes of sugarcane farmers around Camming Sugar Factory, Bone Regency, in managing agricultural waste into value-added organic compost. The main problems identified were the farmers’ habitual practice of burning sugarcane residues, which negatively impacts the environment, and their limited technical ability to convert waste into useful products. The training was conducted using a participatory training approach that actively involved the community in all stages, including theoretical instruction, hands-on composting practice, and mentoring in the use of appropriate technology such as a sugarcane leaf chopping machine. The program’s effectiveness was evaluated through pre- and post-tests using a Likert-scale questionnaire to assess improvements in participants’ knowledge, technical skills, and attitudes. The results indicated a significant increase in average scores from the “fair” category (3.0) to “excellent” (4.5), with the highest improvement observed in technical composting skills. This program also contributed to reducing open-burning practices, improving soil fertility, and stimulating the development of micro-enterprises in agricultural waste management. Overall, the activity aligns with the Sustainable Development Goals (SDGs), particularly Goal 2 (Zero Hunger) and Goal 12 (Responsible Consumption and Production), by promoting circular, environmentally friendly, and sustainable agricultural systems.